The Union State: a changing relationship between Belarus and Russia - Polglase-Korostelev, George (Journal of the Belarusian State University. International Relations, 2020)
In December 2018, the Russian president Vladimir Putin and Belarusian president Alexander Lukashenko agreed to set up an intergovernmental working group on the development of further integration of the Union State A. Lukashenko had been reluctant to yield more Belarusian sovereignty over to Russia. However, a dispute regarding compensating Belarus for a Russian oil tax manoeuvre prompted Moscow to revisit the oldest disagreement: the 1999 Union State Treaty. Russia presented Belarus what sounded like an ultimatum: financial support in return for greater integration with the Russian Federation. This essay will explore the uncertain future and relationship between Belarus and its supposedly closest ally Russia. Chapter one will discuss the early relationship between the countries following the collapse of the USSR. Following that, the second chapter will discuss the relationship between A. Lukashenko and V. Putin and their conflicting ideas of the future of the Union State, up until the 2014 Ukrainian crisis and the deterioration of their relationship. The third chapter will discuss the Russian government’s effort at reviving the Union State, including its successes and shortcomings. The fourth chapter will look at the Belarusian response drawing on some primary research (interviews and official documents analysis) carried out to examine the Belarusian perspective in greater detail. Finally, the essay will conclude with an outlook on the future of the Union State and the relations between Belarus and Russia, using a classical realist approach.